(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the main purposes of this project is to build an intelligent vehicle with safety measures to Prevent Accidents of vehicles. This study discusses about designing a Smart Display and Control (SDC) which will monitor the zone and maintain the specified speed in the zone levels, which runs on an Arduino system. This system includes three modules; automatic fuzzy based speed control module, accident prevention by various sensors and information sending module. Automatic speed control module includes a fuzzy controlled speed controller alongside a light sensor to detect the activities on the road/zone. Information sending module includes GSM and GPS technology. Accident prevention module includes sensory units which ensure the condition of seat belt and the driver. This module includes alcohol sensor and light sensor used alongside speed controller.